Susceptibility of Citrus spp., Quercus ilex and Vitis spp. to Xylella fastidiosa strain CoDiRO. (13th October 2016) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Bjoern; et al.
Abstract: Following a request from the European Commission, the EFSA Plant Health Panel analysed a dossier submitted by the Italian Authorities to reach a conclusion on the status of Vitis spp., Citrus spp. and Quercus ilex as hosts for Xylella fastidiosa strain CoDiRO. The Panel acknowledges the difficulty to provide compelling evidence for non‐susceptibility of a particular plant species. In the case of Vitis spp., the Panel considers that convergent lines of evidence provide sufficient demonstration that at least the tested varieties (Cabernet Sauvignon, Negroamaro and Primitivo) do not support a systemic infection by the CoDiRO strain. The extension of this conclusion to other grapevine varieties and to Vitis species other than Vitis vinifera is associated with significant uncertainties. The Panel therefore considers it premature to conclude that all Vitis species are unable to support a CoDiRO systemic infection. In addition, although the local accumulation detected in the mechanical inoculation experiments may represent an artefact, the Panel considers it premature to conclude that the tested grapevine varieties are not able to support local multiplication of the CoDiRO strain. Further extension of this conclusion to other grapevine varieties and to non‐ vinifera species is also premature. For Citrus spp., the data available provide coherent and converging lines of evidence suggesting that sweet orange may be a non‐systemic host of strain CoDiRO. However, given the limited scope of the data available on other species, the Panel considers it premature to reach a general conclusion for all Citrus species. The potential epidemiological consequences of non‐systemic infections remain to be fully evaluated. In the case of Quercus ilex, the Panel concludes that the limited data available provides some evidence suggesting that it may not be a systemic host of the CoDiRO strain, but that it would be premature to consider this tentative conclusion as firmly established.